The Role of Gestures in the Construction of Meaning in Classroom Context - Menti, Alejandra Beatriz; Rosemberg, Celia Renata (Íkala, Revista de Lenguaje y Cultura, 2017)
This work analyzes the function of gestures produced by teachers and students during the treatment of specific, non-familiar or infrequent vocabulary in primary school social science class. The constant comparative method of qualitative analysis (Glasser y Strauss, 1967) was used in order to analyze interactional sequences in which teacher or students explained or clarified the meaning of a word, corrected the usage of a term or repaired a communication breakdown. The results show that, in the interactional sequences observed, all interlocutors—teacher and students—make gestures when eliciting a specific term, describing particular actions or objects, and elaborating contextual definitions collectively. Even when teachers and students make the same gestures during the treatment of words, the function that these gestures have varies within the interactional sequence.